Gardnerella vaginalis-binding IgA in the urethra of sexually experienced males - Rachel Liu; R. M. Galiwango; Daniel Park; Sanja Huibner; Maliha Aziz; Aggrey Anok; James Nnamutete; Yahaya Isbirye; John Bosco Wasswa; Deo Male; Godfrey Kigozi; Aaron A. R. Tobian; et al. (Microbiome)
Abstract Background Genital inflammation increases HIV susceptibility and is associated with the density of pro-inflammatory anaerobes in the vagina and coronal sulcus. The penile urethra is a critical site of HIV acquisition, although correlates of urethral HIV acquisition are largely unknown. While Streptococcus mitis is a consistent component of the urethral flora, the presence of Gardnerella vaginalis has been linked with prior penile-vaginal sex and urethral inflammation. Here, we use a flow cytometry-based bacterial assay to quantify urethral IgA and IgG that bind G. vaginalis and S. mitis in a cross-sectional cohort of 45 uncircumcised Ugandan men and to evaluate their association with the urethral microbiome and local soluble immune factors. Results Urethral antibodies binding both bacterial species were readily detectable, with G. vaginalis predominantly bound by IgA, and S. mitis equivalently by IgA and IgG. Gardnerella vaginalis-binding IgA was elevated in participants with detectable urethral Gardnerella, with the latter only present in participants who reported prior penile-vaginal sex. In contrast, detectable urethral S. mitis was not associated with sexual history or levels of S. mitis-binding IgA/IgG. The time from the last penile-vaginal sex was inversely correlated with the urethral concentrations of total IgA, G. vaginalis-binding IgA, and chemokines IL-8 and MIP-1β; these inflammatory chemokines were independently associated with higher total IgA concentration, but not with G. vaginalis-binding IgA. Conclusions This first description of microbe-binding antibodies in the penile urethra suggests that urethral colonization by Gardnerella after penile-vaginal sex specifically induces a G. vaginalis-binding IgA response. Prospective studies of the host-microbe relationship in the urethra may have implications for the development of vaccines against sexually-transmitted bacteria. Video Abstract